Migration Behavior of Rural Youth from Agriculture in North Coastal Andhra Pradesh - Sai, Malluri; Prusty, Ajay Kumar; Padhy, Chitrasena; Reddy, Idemakanti Chandrakanth (Indian Journal of Extension Education, 2024)
Due to increased industrialization, a growing service sector, improved food security, easier access to healthcare and educational opportunities in cities, and growing young ambitions, the migratory norm of rural youth has been continuously rising over the past 25 years. The study conducted during 2023 aimed to ascertain youth migration patterns from the rural districts of Srikakulam and Vizianagaram in Andhra Pradesh. The results showed that the main reasons behind youth movement from rural areas were inconsistent income, low employment, and recurrent crop failures. The respondents have shown a medium level of attitude towards agriculture. The Direct indicators with a mean average of (2.23) and perception migration indicators with a mean average of (2.88) have been noticed. Independent variables such as age, farming experience, proximity to towns/cities, annual income, self-reliance, and self-confidence were positively correlated. A positive significance level has been found for education, occupation, farm skill, years of stay in native, migration experience, economic motivation, achievement motivation, and income expectancy, which are negatively correlated with non-farm skills and risk orientation.